Femoral Physeal-Sparing Anterior Cruciate Ligament Reconstruction Using the Iliotibial Band: Over-The-Top Technique - Felipe Galvão Abreu, M.D.; Charles Pioger, M.D.; Florent Franck, M.D.; Benjamin Freychet, M.D.; Thais D. Vieira, M.D.; Bertrand Sonnery-Cottet, M.D. (Arthroscopy Techniques, 2020)
Anterior cruciate ligament injuries are increasingly frequent in skeletally immature patients. However, treatment within this subpopulation remains controversial. Conventional transphyseal reconstruction techniques have been questioned because of potential physeal injuries. Conservative treatment, on the other hand, may lead to degenerative meniscal and chondral lesions. This Technical Note describes the femoral physeal-sparing over-the-top technique using an iliotibial band. It is a safe and effective method for anterior cruciate ligament reconstruction in skeletally immature patients.